Effect of season and period on semen characteristics of two and three breed Gir crosses - BHOTTE, U Y; SUTAR, D A; ULMEK, B R (The Indian Journal of Animal Reproduction, 2005)
The present investigation was undertaken on 4931 ejaculate records pertains to halfbred and triple cross bulls maintaindat Research-cum-Development Project on Cattle, Rahuri. The overall means of semen volume (Ml), sperm motility (0-5 scale) andper cent live spermatozoa in IFG (50% Holstein-Friesian + 50% Gir Interse), IFJG (50% Holstein-Friesian + 25% Jersey + 25% GirInterse), IJFG (50% Jersey+ 25% Holstein-Friesian + 25 Gir Interse) and IBFG (50% Brown Swiss + 25% Holstein-Friesian + 25%Gir Interse) were 5.040±0.106, 3.172±0.106, 3.172±0.018 and 76.458±0.250, 4.508±0.039, 3.267±0.016 and 77 .344±0.189;3.887±0.063, 2.639±0.026 and 71.145±0.321 and 5.170±0.071 , 3.380±0.023 and 78.489±0.297, respectively. The effect ofseason on semen volume, sperm motility and per cent live spermatozoa was nonsignificant in all the genetic groups under studyHowever, the influence of period of semen collection on the traits was significant in all the groups.
Keywords: Semen characteristics; Gir crosses bulls